Implementation of Swot Analysis in Determining Strategy at PT HAN - Vanadya, Melvina; Agustini, Maria Y. D. Hayu (Journal of Management and Business Environment (JMBE), 2024)
The expedition industry has been experiencing rapid growth because of the increase on purchase online that generates higher demand on distribution services. PT HAN operating in the industry is however has experienced a continuous sales decline. This research is aimed at determining effective strategy for PT HAN to increase its sales. Interview with the key informants in the company was to explore the information on strategy formulation. A list of questions formed according to the strategy formulation process in strategic management was prepared as guidance. The interview transcription was the data to be analyzed using SWOT matrix to identify alternative strategies that are effective for the company to increase its sales. This alternative strategies resulted are to implement home services, to increase the number of branches, to rejuvenate the armadas, to regenerate the business, and to create a tracking system. It is estimated that the company can grow the business by implementing the strategies.